Hobbes y el problema del realismo metafísico - Defez i Martín, Antoni (Logos. Anales del Seminario de Metafísica, 2002)
In this paper a non-paradoxical interpretation of Hobbes’s defence of scientific realism of materialistic type is proposed. It attempts to explain how this author was able to defend the truth of materialism and at the same time to deny that it could be demonstrated in a metaphysical way. The key to his position depends on the metaphorical use of the concept of ‘imitation’ and the treatment of the infinite and irresistible power as the philosophically relevant attribute of God. So Hobbes’s intention would consist of saying that the explanation, but not the demonstration, of the truth of materialism depends on the ontological parity and continuity between the world and the human being, in the way in which they are explained by empirical science. In this sense Hobbes’s project, very different to Descartes’s one, would be an attempt to naturalise the epistemology that yet is conscious of the metaphysical limits affecting the naturalistic proposals of philosophy.